Conflict, Cooperation, and Institutional Change on the Commons - Coleman, E.A.; Mwangi, E. (Wiley, 2015)
Rational choice scholarship posits two principal theories to explain why political institutions emerge and change: cooperation theory and conflict theory. We evaluate cooperation theory and conflict theory to explain the emergence of common property institutions among a group of Maasai pastoralists in southwestern Kenya. Our empirical results show that the change to common property is best explained by conflict theory.